Sports officials and officiating: science and practice - MacMahon, Clare; Mascarenhas, Duncan; Plessner, Henning; Pizzera, Alexandra; Oudejans, Raôul R. D.; Raab, Markus (Taylor and Francis, 2014)
Sports officials (umpires, referees, judges) play a vital role in every sport, and sports governing bodies, fans, and players now expect officials to maintain higher professional standards than ever before. In this ground-breaking book, a team of leading international sport scientists and top level officials have come together to examine, for the first time, the science and practice of officiating in sport, helping us to better understand the skills, techniques and physical requirements of successful refereeing.The book covers every key component of the official's role, including:Training and
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Schiedsrichter; Sportrecht